Fujifilm X-T2 - Pfirstinger, Rico (Rocky Nook, 2016)
In this book, popular Fuji Rumors "X-Pert Corner" columnist Rico Pfirstinger teaches about the little-known capabilities of the Fujifilm X-T2, which he's discovered through months of in-depth research and experimentation with the camera. After a brief overview of the camera's basic functions, Rico cuts to the chase and provides a plethora of tips and practical instructions not found in the user's manual. With this knowledge, you will be able to take full advantage of the capabilities of the X-T2. The Fujifilm X-series cameras have amazing features but may require an adjustment period for those new to using these cameras, even photographers who have been lifetime shooters. This guide will help you to quickly feel comfortable using your camera so that you can achieve excellent results. Topics covered include: Menu shortcuts; Long exposures; Firmware upgrades; Hybrid autofocus system; Auto and manual focusing; Face detection; ISOless sensor; Dynamic Range expansion; Film simulations; Custom settings; RAW conversion; Panoramas; Movies; Self-timer; Flash; Adapted lenses; And much more ...
Print version record
Keywords: Photography; Photography -- Digital techniques; Photographie; photographic techniques